The New Narrative of International Terrorism in Africa: Answers and Impact (Comillas Journal of International Relations, 2018)
Under the “new wars” paradigm, contemporary armed conflicts in the African continent have been stripped of their political and ideological dimension, and the motivations of the actors involved have been reduced to economic greed and identity rivalries. After the attacks of 9/11, a narrative has appeared focusing on extremist violence and international terrorism in the African continent. This diagnosis has triggered the deployment in different parts of the continent of different antiterrorist strategies, both regional and international. In the present article we will draw a map of this extremist violence, present nowadays in some regions of the continent, along with the anti-terrorist strategies deployed, in order to analyse their impact, to validate or deny the diagnosis of this narrative and to confront it to other views.
Keywords: Sub-Saharan Africa; international terrorism; anti-terrorism strategies